Betulinic Acid Protects From Bone Loss in Ovariectomized Mice and Suppresses RANKL-Associated Osteoclastogenesis by Inhibiting the MAPK and NFATc1 Pathways - Wei, Jiyong; Li, Yicheng; Liu, Qian; Lan, Yanni; Wei, Chengming; Tian, Kun; Wu, Liwei; Lin, Chunbo; Xu, Jiake; Zhao, Jinmin; Yang, Yuan (Frontiers in Pharmacology, 2020)
Osteoclasts with elevated bone resorption are commonly present in postmenopausal osteoporosis, and other osteolytic pathologies. Therefore, suppressing osteoclast generation and function has been the main focus of osteoporosis treatment. Betulinic acid (BA) represents a triterpenoid mainly purified from the bark of Betulaceae. BA shows multiple biological activities, including antitumor and anti-HIV properties, but its effect onosteolytic conditions are unknown. In this study, we found that BA inhibited receptor activator of nuclear factor‐κB ligand (RANKL) ‐associated osteoclastogenesis and bone resorptive function, as assessed by tartrate‐resistant acid phosphatase (TRAP) staining, fibrous actin ring formation, and hydroxyapatite resorption assays. Mechanistically, BA downregulated the expression of osteoclastic-specific genes. Western blot analysis revealed that BA significantly interrupted ERK, JNK and p38 MAPK activation as well as intracellular reactive oxygen species (ROS) production, thus altering the downstream induction of c-Fos and NFATc1. Corroborating the above findings in cell-based assays, BA prevented ovariectomy-associated bone loss in animal models. In conclusion, these findings suggest that BA can inhibit osteoclast generation and function as well as the RANKL signaling pathway, and might be used for treating osteoclast-related osteoporosis.